2015
DOI: 10.1519/jsc.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

Match-Play Demands of Elite Youth Gaelic Football Using Global Positioning System Tracking

Abstract: Global positioning systems (GPS) technology has made athlete-tracking a convenient and accepted technique to specify movement patterns and physical demands in sport. The purpose of this study was to examine positional demands of elite youth Gaelic football match-play using portable GPS technology to examine movement patterns and heart rates across match periods. Fifty-six elite youth male Gaelic footballers (age, 15 ± 0.66 years) fitted with portable 4-Hz GPS units were observed during 6 competitive matches (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
4
30
0
2
Order By: Relevance
“…Having said this, an understanding of the physiological demands and movement patterns during match play will aid coaches in the development of sport-specific training strategies for young players. The mean distance covered by U-18 players in this study is similar to that reported in younger (U-15) Gaelic football players (39). Elite adult Gaelic football players cover 8.5 km during 70-minute matches (30).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Having said this, an understanding of the physiological demands and movement patterns during match play will aid coaches in the development of sport-specific training strategies for young players. The mean distance covered by U-18 players in this study is similar to that reported in younger (U-15) Gaelic football players (39). Elite adult Gaelic football players cover 8.5 km during 70-minute matches (30).…”
Section: Discussionsupporting
confidence: 83%
“…Despite the widespread adoption of GPS technology in team sports, surprisingly few studies have been published on the physiological demands and activity profiles during Gaelic football matches (21,30,32,36,42) and only 1 study has involved players #18 years (39). Reilly et al (39) evaluated the physiological demands and activity patterns during match play in youth (U-15) Gaelic football players. The study found that players performed at an intensity equating to 85% of HR maximum (HRmax) and covered an average distance of 5,732 6 1,047 m during 60-minute competitive matches.…”
mentioning
confidence: 99%
“…The sport is played with an amateur ethos super imposed on a professional work ethic (9) . Gaelic football is a team based invasion field game that entails a wide range of offensive and defensive skills to be executed at high speed as play shifts rapidly (38,39) . The competitive elite Gaelic football season takes place over an eight month period.…”
Section: Introductionmentioning
confidence: 99%
“…Without many sport-specific published studies as reference, Gaelic football coaching staff preparing and prescribing training loads will rely on personal experience or anecdotal observations (38) . Therefore, inference as to the running performance of players has been appraised from other field sports due to apparent similarities in locomotion characteristics (8, …”
Section: Introductionmentioning
confidence: 99%
“…The representative teams of London and New York are made up largely of Irish emigrants who live in the respective cities. No youth teams from either New York or London currently participate in any of the major competitions at youth level in Ireland. Research to date in Gaelic games has focused on injury incidence (Blake, Murphy, Gissane, & O'Malley, 2011;Murphy, Gissane, & Blake, 2012), anthropometric profiles (Collins, Reilly, & Morton, 2014;Kelly & Collins, 2015), technical performance indicators (Bradley & O'Donoghue, 2011;Carroll, 2013), and physical demands (Collins & Doran, 2015;Malone, Solan, Collins, & Doran, 2016;Reilly, Akubat, Lyons, & Collins, 2015). While anthropometric data and performance indicators can give an insight into Gaelic football, the data can be influenced by the level and quality of the teams that are sampled.…”
Section: Introductionmentioning
confidence: 99%